Environmental efficiency of rice production in Vietnam: An application of SBM-DEA with undesirable output - Truc-Linh Le; Thi-Thuy-Hai Luu; Nga Huynh; Rebecca H. Chung (Society for Indonesian Biodiversity, 2020)
Abstract. Le TL, Luu TTH, Huynh N, Chung RH. 2020. Environmental efficiency of rice production in Vietnam: An application of SBM-DEA with undesirable output. Biodiversitas 21: 2710-2715. In Vietnam, the agricultural sector is one of major sources of the country’s greenhouse gas (GHG) emissions and over half of that comes from rice cultivation. This study evaluates the environmental efficiency of 400 rice farms in the Mekong Delta using slack-based measure (SBM) data envelopment analysis (DEA) with considering the total amount of CO2-equivalent (CO2-eq) emissions in the rice field as undesirable output. The findings revealed that the average environmental efficiency score of the farmers was very low, just only 0.461. Only 2.25% of the sample farms were environmentally efficient while majority of them (58%) obtained the efficiency values less than the mean indicating that their environmental efficiency needs to be further improved. The small rice farms were higher in environmental efficiency scores compared with large farms. The sample rice farmers who are members of agricultural cooperatives obtained a significantly higher environmental efficiency than the non-cooperative members. The estimated results of input and bad output excesses showed that about 1.35 tons of CO2-eq ha-1 could be reduced and an average of 54.18 kg N ha-1 could be saved in order to improve the environmental performance of rice production in the study area.